Incidence of hailstorms damage and strategies to minimize its effects on large cardamom (Amomum subulatum Roxburgh) plantations in Sikkim, North East India - GUDADE, B.A.; BABU, SUBHASH; AAGE, A.B.; BORA, S.S.; DEKA, T.N.; SINGH, NUTTAM; KUMAR, AMIT; SINGH, RAGHAVENDRA; DHANAPAL, K.; REMASHREE, A.B. (MAUSAM, 2023)
Among the extreme weather events, hailstorm in recent past caused significant damage of large cardamom crop in Sikkim. In high altitude area of Sikkim, hailstorms generally occurrs in the month of March and April and caused severe damage to large cardamom plantations. In this paper, a detailed account of incidence of hailstorm damage and strategies to minimize its effects on large cardamom plantations are discussed. Frequency distribution of hailstorm showed that during last eight years hailstorm in Pangthang area of Sikkim occurred between 1427 to 1532 hrs and it continued for around 37 minutes on average. However, in Kabi area of North Sikkim hailstorm generally occurs during 1621 to 1628 hrs and it continues for around 21.25 minutes. Hailstorms varied in size from 0.5 to 1.0 cm in diameter. Damage caused by the hailstorms on plant tissue depends mainly on its size, duration of the storm event and the condition of the plant tissue when the injury occurs. Large cardamom being a broad leaved plant, the lamina tears parallel to the veins. Physical damage to floral parts of large cardamom plants due to hailstorm occurred at the flowering stage and depending on the extent of damage the yield of the plant was also affected in the subsequent crop season. Frequent hail episodes are identified and measures to minimize the damage of large cardamom plantations are discussed. The information generated in this study was found to be very useful in minimizing large cardamom crop loss through operational agromet services launched by the India Meteorological Department/Ministry of Earth Sciences in collaboration with the Agromet Field Units (AMFUs) located at Gangtok and ICAR-NOFRI, Tadong through Krishi Vigyan Kendra-East Sikkim, Ranipool.